MENINGKATKAN KREATIVITAS SERTA KECERDASAN DALAM SENI KARYA DAN BAHASA INTERNASIONAL BAGI ANAK-ANAK DESA LUWUK GUNUNGSARI BANTEN - Ria Resti Fauji; Aluffikri Aluffikri; Siti Murnah; Putri Rizki Arofiq; Jaka Wijaya Kusuma; Hamidah Hamidah (LPPM Universitas Bina Bangsa, 2022)
The initial stage carried out by TIM Pengabdi students was to ask permission from the village office and stay in touch with the head of the Luwuk village for us to serve in the community and carry out activities in the village, then we looked for a place/post for us (TIM Pengabdi) to rest for more than a month and After that, we stay in touch with Mr. RT/RW, youths, villagers and village children in the village to carry out work programs that we make, one of which is in the field of education and skills, especially during the Covid-19 pandemic, all learning is done online. good for PAUD/TK, SD, SMP, SMA/SMK levels, Even in lectures, you can learn online via whatsapp group, zoom, google meet, google classroom and many other online applications coupled with programs made by the government to reduce the spread of Covid-19 with the Implementation of Community Activity Restrictions (PPKM) not only adults who feel bored/tired of the rules but the children in Luwuk village feel the same way because while at home for that, TIM Pengabdi does a work program, one of which is the work made by the children of Luwuk village by going offline/doing activities at the command post while still following health protocols ( keeping a distance, using masks and washing hands) both in learning English and in doing handicrafts made of flannel. Straws, cardboard, origami paper, etc. With this program of activities to increase creativity, innovation, thinking patterns / development of creative ideas, increase knowledge / insight in international languages, eliminate boredom by making works and increase intelligence for children in Luwuk village